Digital-image-correlation-based thermomechanical diagnostics of Bismuth Telluride pillars in a thermoelectric cooler. (April 2022) - Zhang, Yiyuan; Li, Wenlan; Gao, Zeren; Liu, Yang; Zhang, Peng; Zhao, Yang
Highlights: Digital image correlation based on laser speckle proves suitable for thermomechanical diagnostics of TEC pillar. Direct observation of full-court pillar-level deformation is achieved Thermally induced global displacement and strain fields of TEC pillar are obtained. Maximum shear stress exceeds the fracture limit. Abstract: Fatigue-induced fracture of B i 2 T e 3 pillars in a thermoelectric cooler (TEC) due to thermal stress is a prevailing occurrence in the device during dynamic operation, which has been a major reliability concern from manufacturing perspectives. However, it remains a crucial challenge to explore global pillar-level deformation of TEC with simple experiment methodology. Herein, digital-image-correlation-based thermomechanical diagnostics is introduced to experimentally characterize the in-plane thermal deformation of B i 2 T e 3 pillars. Highly contrasted surface pattern generated by He-Ne laser was utilized, exempted from extra speckle fabrication while simultaneously guaranteeing high experimental accuracy. By imposing different thermal loadings to specimen, corresponding full-court pillar-level displacements are respectively observed. Furthermore, shear strain and stress distribution and their dependence on Δ T are studied with stress concentration region identified. The maximum in-plane shear stress at around Δ T = 60 K is indicated to exceed material fracture limit, resulting in high probability of fracture. The good agreement of experimental results and empirical simulation indicates the viability of the proposed technique. Due to its capability of direct observation of thermomechanical behavior of B i 2 T e 3 pillars, the approach employed in this study is of significant practical appeal and notable potential for thermal reliability prediction of thermoelectric device.